Analisis Kinerja Konsultan Pengawas pada Proyek Rekonstruksi Jalan Puguk–Lubuk Resam di Provinsi Bengkulu - Adi Wijaya; Rezi Munizar (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Road infrastructure development requires effective supervision to ensure project quality, schedule, cost, and occupational safety. This study aims to analyze the performance of supervision consultants in the Puguk–Lubuk Resam Road Reconstruction Project, Bengkulu Province. A quantitative descriptive approach was employed. Data were collected through field observations, documentation, and questionnaires distributed to 56 respondents consisting of supervision consultants, contractors, and project owners' representatives. Descriptive statistical analysis was conducted using seven performance indicators. The results indicate that all indicators achieved good to very good performance, with scores exceeding 80%. Technical specification comprehension obtained the highest score (85.6%), while labor supervision recorded the lowest score (82.6%) but remained within the good category. The findings demonstrate that technical competence, stakeholder coordination, and effective supervision significantly contribute to successful road construction project implementation.